Hate Speech Di Media Sosial Dalam Kerangka Komunikasi Pendidikan: - - Rifa'i; Sari, Widia (EDUCATE : Journal of Education and Culture, 2024)
Abstract: The increasing number of internet users has a negative impact, one of which is hate speech, so that from year to year on social media the number of hate speech continues to increase without any signs of disappearing or being resolved. Hate speech is an action that is contrary to the communication function of education as an indicator of intelligence and communication ethics. This research aims to describe forms of hate speech on social media as well as analyze hate speech in educational communication in posts by Twitter social media users. The method used in this research is descriptive qualitative. Research data was obtained through listening, taking notes, and documenting uploads and comments from Twitter account users. The results of this research show that there is hate speech on social media in the form of videos, comments, and tweets. In the form of insulting speech, defamation, incitement, provocation, spreading false news, and blasphemy. So educational communication is needed to minimize acts of hate speech by involving educational communication functions including informative functions, educational functions, persuasive functions, and expressive functions. Keywords: educational communication, hate speech